Ways and means of implementing budgetary reform in Algeria under the organic law 15-18 - Bey, Kadda; Berrais, Khalifa (The International tax journal, 2026)
<!--StartFragment--> The reform of Algeria's general budget under Organic Law 18-15, which regulates financial laws, is a new approach that will undoubtedly contribute to building a legal framework that supports the country's financial and economic transformations. Through these reforms, the state seeks to keep pace with the global financial system, especially after Law 84-17 proved inadequate in adapting to internal and external changes. The management based on the allocation of resources has been abandoned in favour of achieving objectives and financial sustainability through the adoption of multi-year budget planning, with the need to improve public resource management and enhance transparency and accountability. Budgetary reform in Algeria has encountered a number of obstacles to the achievement and implementation of public administration governance, and a number of challenges must be overcome in order to achieve the desired objectives of this reform.